Perceived stress related to nursing education and its influence on nursing students’ academic and clinical performance. - Gurbinder Kaur, JS; Hamidah, H; Blackman, I; Wotton, K; Belan, I (Penerbit UKM, 2011)
Stress has a negative effect on student nurses well-being and can impede learning or motivate them and is conducive to learning. This study examined the perceived stress and factors that influenced daily students’ life among both the Diploma and Bachelor of Nursing students. A total of 241 nursing students were involved in this research project. Findings of this study indicated that junior nursing students (<21 years) of both cohorts perceived significantly more stress than older (≥21 years) nursing students. Second year students of the Diploma group claimed being more stressed than their peers (1st and 3rd years). Personal problems were the main issue of concern among the second year Diploma students. Workload of nursing education and fear of failing the nursing programme were the major stressors among the first year nursing students of the Bachelor cohort as compared to their seniors. A mixture of negatively and positively significant correlations was observed between academic work and clinical scores among the Diploma and Bachelor of Nursing students respectively. Both the Diploma and Bachelor of Nursing students’ stress did not influence their GPA scores. Negatively significant correlation was noted between stress and clinical scores among the Diploma of Nursing students. A negatively significant correlation was found between age and CGPA scores among the Bachelor cohort. Both male and female Diploma and Bachelor nursing students perceived no differences in stress related to their academic work. The findings of this study provide important information for nursing education at the institute examined in this study, and have implications for future research.